2018
DOI: 10.1080/02670844.2018.1430010
|View full text |Cite
|
Sign up to set email alerts
|

Surface mechanical coating of Cu plate by Cu Al powders

Abstract: Through Surface Mechanical Coating (SMC), a plate of pure Cu was successfully coated using of Al-50-wt% Cu during mechanical alloying. Effect of milling time and heat treatment on formation of coating at 1050 °C was investigated. Compositional and microstructural study of the coating and its properties were conducted by means of X-Ray Diffraction (XRD), Microfocus XRD, Scanning Electron Microscopic (SEM), Electron Probe Micro-Analyzer (EPMA), Transition Electron Microscopic (TEM), and Vickers Microhardness tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In recent years, nanocrystalline (NC) materials have attracted widespread attention due to their excellent mechanical [1][2][3][4][5][6][7], electrical [8,9], magnetic [9,10], and radiation tolerance [7,11] properties. Experimental results have demonstrated that NC materials can be produced by equal-channel angular pressing [12], high-pressure torsion [13,14], mechanical alloying [15][16][17], and nanoindentation [18]. However, a major disadvantage of conventional NC materials is their limited thermal stability, which prevents their use in high temperature applications [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nanocrystalline (NC) materials have attracted widespread attention due to their excellent mechanical [1][2][3][4][5][6][7], electrical [8,9], magnetic [9,10], and radiation tolerance [7,11] properties. Experimental results have demonstrated that NC materials can be produced by equal-channel angular pressing [12], high-pressure torsion [13,14], mechanical alloying [15][16][17], and nanoindentation [18]. However, a major disadvantage of conventional NC materials is their limited thermal stability, which prevents their use in high temperature applications [19][20][21].…”
Section: Introductionmentioning
confidence: 99%